Предмет: Алгебра, автор: daikityanmeow

1
a)(x-4)(x+4)-2x(1+x)
б)(x-y)^2-x(x+2y)
в)8c+4(1-c)^2

2
a)2a^3-2ab^2
б)4x^2-8xy+4y2

3
(4y^2+3)^2-6y(4-y)+(2y-3)(2y+3)

Ответы

Автор ответа: sandi654
1

Ответ:

1.

а) x² + 4x - 4x - 16 - 2x - 2x²= -x² - 2x - 16;

б)(x-y)²-x(x+2y) = x² - 2xy + y² - x² - 2xy = -4xy + y²;

в)8c+4(1-c)² = 8c + 4(1+2c+c²) = 8c + 4 + 8c + 4c² = 4c² + 16c + 4;

2.

a)2a³-2ab² = 2a(a² - b²) = 2a(a-b)(a+b)

б)4x²-8xy+4y² = (2x - 2y)² ;

3.

(4y²+3)²-6y(4-y)+(2y-3)(2y+3) = 16y⁴ + 24y² + 9 - 24y + 6y² + 2y²-9 = 16y⁴ + 32y² - 24y;

8y(2y³+4y-3)

Объяснение:

Похожие вопросы
Предмет: Окружающий мир, автор: Nastya34557890